"The Power of Metaphor: Exploring the Impact of Figurative Language in Literature" (Texas Journal of Philology, Culture and History, 2024)
"The Power of Metaphor: Exploring the Impact of Figurative Language in Literature" is a scholarly article that delves into the profound influence of metaphors in literary works. This comprehensive exploration highlights how metaphors go beyond literal language, creating vivid imagery and conveying complex ideas. The article discusses the emotional impact of metaphors, their role in symbolism and subtext, and their ability to bridge the gap between the concrete and the abstract. It also addresses the cultural and contextual significance of metaphors. Overall, this article offers valuable insights into the artistry and power of metaphors, making it a valuable resource for scholars and enthusiasts interested in figurative language's impact on literature.